2017
DOI: 10.1186/s12890-016-0360-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of treadmill exercise versus Flutter® on respiratory flow and sputum properties in adults with cystic fibrosis: a randomised, controlled, cross-over trial

Abstract: BackgroundTreadmill exercise and airway clearance with the Flutter® device have previously been shown to improve mucus clearance mechanisms in people with cystic fibrosis (CF) but have not been compared. It is therefore not known if treadmill exercise is an adequate form of airway clearance that could replace established airway clearance techniques, such as the Flutter®. The aim of this study was to evaluate respiratory flow, sputum properties and subjective responses of treadmill exercise and Flutter® therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 38 publications
2
62
0
Order By: Relevance
“…In the present study, we found no differences in sputum viscoelasticity between the two experimental conditions, thus rejecting our initial hypothesis. Two previous studies reported altered sputum viscoelasticity after an acute bout of treadmill exercise or Flutter® and treadmill exercise compared to resting breathing in adults with CF [6,11]. Treadmill but not cycling exercise reduced sputum viscoelasticity and trunk oscillations during treadmill running/walking have been postulated as a possible underlying mechanism [11].…”
Section: Sputum Rheological Properties and Exercisementioning
confidence: 99%
See 4 more Smart Citations
“…In the present study, we found no differences in sputum viscoelasticity between the two experimental conditions, thus rejecting our initial hypothesis. Two previous studies reported altered sputum viscoelasticity after an acute bout of treadmill exercise or Flutter® and treadmill exercise compared to resting breathing in adults with CF [6,11]. Treadmill but not cycling exercise reduced sputum viscoelasticity and trunk oscillations during treadmill running/walking have been postulated as a possible underlying mechanism [11].…”
Section: Sputum Rheological Properties and Exercisementioning
confidence: 99%
“…Exhalation through the Flutter® causes oscillation of the steel ball and produces rhythmic variations in positive expiratory pressure of 10 to 25 cm H 2 O [28,29]. Flutter® therapy increases peak expiratory flow and creates an expiratory airflow bias in CF [6], initiating mucociliary clearance mechanisms.…”
Section: Flutter® Breathing Therapymentioning
confidence: 99%
See 3 more Smart Citations